Examining the Effects of Presentation Patterns, Orders, and Information Types in Investment Decision Making - Almilia, Luciana Spica; Hartono, Jogiyanto; Supriyadi, .; Nahartyo, Ertambang (Gadjah Mada International Journal of Business, 2013)
This study aims to investigate the existence of Belief Model (BAM) developed by Hogarth and Einhorn (1992) in investment decision making. Particulary, this study examined: the effects of presentation patterns, presentation orders, and information types (accounting or non-accounting information) in investment decision making. This study used laboratory experiment to test the hypotheses. Hypotheses were tested using t-test. This study showed a âjudgement biasâ that is a recency which the effect of presentation pattern is consecutive is higher than unconsecutively.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â